A novel predictive model for multiaxial fatigue in carburized bevel gears. Issue 8 (17th April 2021) - Böhme, Stephan André; Vinogradov, Alexei; Papuga, Jan; Berto, Filippo
Abstract: This publication focuses on the numerical stress prediction in case‐carburized bevel gears and on their fatigue assessment. Four gear sets are analyzed for the common fatigue failure modes of pitting, tooth root breakage, and subsurface fatigue. The proposed algorithm, enabling the prediction of the dominant failure type and region, relies on the previously published material model for carburized CrNiMo steels. It utilizes a 2D plane strain simplification as only the mean cross‐section is analyzed and evaluates the shear mean and amplitude stresses through the maximum rectangular hull method. A novel multiaxial fatigue criterion is presented and validated.